Karl Popper e o problema da probabilidade - Diego Henrique Figueira de Melo (2015)
This work has as its goal the study and understanding of the role of propensity theory (Karl Popper's thesis) in the fundamentals of probability calculus. For the execution of such proposal, this work was organized in three parts. The first chapter provides a basic review of fundamentals of probability calculus and some of its properties. In this first part it also addresses the debate between subjectivism and objectivism in contemporary philosophy of probability, showing how the different interpretations (classical, logical, subjectivist and frequentist) fit in the proposed debate. The second chapter is dedicated to the problem of induction and its relationship with some probabilistic approaches, such as logic and frequency theory. The study starts from the epistemological problem of inductive reasoning validation (from Hume to contemporary formulations) and shows possible probabilistic solutions to this issue. This second part also covers Popper's attacks on inductive reasoning, both in the epistemological perspective as in the probabilistic perspective. In the last chapter propensity theory is presented and analyzed, as well as its solutions to the problems portrayed throughout the work. Propensity theory subscribes to the objectivist camp of the present debate, it arised from the need Karl Popper found to strengthen the arguments of frequency theory against subjectivist attacks.